KoMus and KOPRA-M: psychometric analysis of two musical competency tests adapted for Norwegian primary school students - Nørstebø, Kirsti; Knigge, Jens (Frontiers in Education, 2024)
This paper presents Norwegian adaptations of the KoMus and KOPRA-M assessments designed to evaluate music-related competencies. Our research delves into the assessments' alignment with the curriculum and investigates the psychometric properties of the Norwegian versions using a sample of Norwegian fifth graders (KoMus: N = 374, KOPRA-M: N = 370). Furthermore, it provides practical illustrations of how these item response theory (IRT)-based assessments can be employed, including competency-level examples. The Norwegian short versions of the KoMus and KOPRA-M tests demonstrated robust psychometric characteristics (especially in terms of reliability, model, and item fit), making them promising instruments for the deeper exploration of musical competency within primary and lower secondary school contexts.